2014
DOI: 10.5489/cuaj.1764
|View full text |Cite
|
Sign up to set email alerts
|

Long-term complications in men who have early or late radiotherapy after radical prostatectomy.

Abstract: Introduction: Choosing adjuvant radiotherapy (RT) or salvage RT after radical prostatectomy (RP) for locally advanced prostate cancer is controversial. Performing RT early after RP may increase the risk of urinary complications compared to RT performed later. We evaluated the urinary complication rates of men treated with surgery followed by early or late RT. Methods: Using a retrospective chart review, we compared rates of urinary incontinence (UI), bladder neck contracture (BNC), or urethral stricture in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Sowerby and colleagues reported a VUAS rate following adjuvant or salvage radiotherapy of 2.6%. 30 Although they demonstrated no difference in rate when delivered in an adjuvant or salvage setting, delaying the administration of radiation after RP has been shown by others to decrease the rate of VUAS. 31,32 Several patient factors have been associated with VUAS in different surgical series.…”
Section: Epidemiologymentioning
confidence: 99%
“…Sowerby and colleagues reported a VUAS rate following adjuvant or salvage radiotherapy of 2.6%. 30 Although they demonstrated no difference in rate when delivered in an adjuvant or salvage setting, delaying the administration of radiation after RP has been shown by others to decrease the rate of VUAS. 31,32 Several patient factors have been associated with VUAS in different surgical series.…”
Section: Epidemiologymentioning
confidence: 99%
“…Whereas, retrospective studies focusing on patients treated with SRT showed that this radiotherapy might lead to grade 2 or higher genitourinary toxicities in up to 20% of the patients [34,35]. In addition, previous studies that compared the safety profile of postoperative ART and SRT failed to show significant differences between both approaches [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In that series, only 96 of the 652 (15%) patients received IMRT. 24 It is possible that over the next 10 years more patients will be treated with IMRT rather than 3D-CRT, which may reduce the incidence of cuff erosion. Nevertheless, from December 2001 to January 2012, our cohort of patients treated with radiation after RP who subsequently required an AUS had a significantly increased risk of cuff erosion compared to those who did not receive radiotherapy.…”
Section: Discussionmentioning
confidence: 99%